Managing nirmatrelvir/ritonavir during COVID-19: pharmacists' experiences from the Perak state of Malaysia - Chee Tao Chang; Su Yin Ong; Xin Jie Lim; Lan Sim Chew; Philip Rajan (Taylor & Francis Group, 2022)
Novel therapeutic agents for SARS-CoV-2 have emerged over time, serving to reduce the severity of the disease, admission and mortality, especially among high-risk populations. Oral nirmatrelvir/ritonavir (Paxlovid®) was found to reduce the risk of disease progression. Pharmacists played multiple roles in handling the COVID-19 pandemic. This article highlights the roles of pharmacists in managing nirmatrelvir/ritonavir within the Malaysian context. Pharmacists were actively involved in Paxlovid® inventory management. To ensure the balance between supply and demand of new therapeutic drugs, pharmacists in health facilities constantly monitor the inventory levels of the medications. As Paxlovid® was initially reserved for a certain population who met the clinical eligibility criteria based on a scoring system, pharmacists were required to screen and exclude patients with non-indications or contraindications to the medication. During dispensing, pharmacists convey clear instructions on how to take the medications to ensure adherence and medication safety. The novel nature of the medications necessitates pharmacists to counsel patients regarding its indication, the mode of action, actions to take when missing a dose or overdose happens, side effects, storage and disposal methods, as well as mechanism of reporting adverse drug reactions. Pharmacists were required to follow-up all patients via phone call on Day 3 and Day 5 post-initiation, examining both adherence and adverse drug reactions associated with Paxlovid®. Pharmacists experienced multiple challenges in managing Paxlovid®, particularly due to increased workload, suboptimal follow-up response, stringent medication storage requirements, and adherence issues. Universal research and innovation initiatives were proposed to improve the delivery of novel therapeutic agents in the future health system.